Smart Home Energy Management using BEVSE for Vehicle-to-Home (V2H) Systems - Ketjaem, Supakorn; Khomfoi, Surin (My University, 2025)
This paper presents a method for managing household energy consumption and production in homes utilizing electric vehicles (EVs). The approach integrates a Home Energy Management System (HEMS) with Bidirectional Electric Vehicle Supply Equipment (BEVSE), which enables both charging and discharging of EVs using Vehicle-to-Home (V2H) and Vehicle-to-Grid (V2G) technologies. These technologies allow EVs to supply power to household appliances and feed energy back into the grid while ensuring that energy consumption and distribution remain within the meter's capacity limits. Simulation results from MATLAB Simulink demonstrate that this approach helps prevent potential damage to the power system, mitigates energy shortages, and enhances grid stability.
Keywords: Bidirectional Electric Vehicle Supply Equipment; Home Energy Management System; Vehicle to Grid; Vehicle-to-Home